2005
DOI: 10.1128/jvi.79.21.13285-13297.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Major Determinant for Membrane Protein Interaction Localizes to the Carboxy-Terminal Domain of the Mouse Coronavirus Nucleocapsid Protein

Abstract: Coronavirus assembly results from an accumulation of interactions among four structural proteins, the positive-sense RNA genome, and a host membrane envelope obtained from the site of budding, which is the endoplasmic reticulum-Golgi intermediate compartment. Three of the four structural proteins are embedded in the virion envelope: the spike protein (S), the membrane protein (M), and the small envelope protein (E). The fourth, the nucleocapsid protein (N), resides in the virion interior, wrapping the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
163
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(176 citation statements)
references
References 47 publications
13
163
0
Order By: Relevance
“…Through its interactions with the viralRNA, the M protein and itself, N plays important roles in virus assembly (Escors et al, 2001;Hurst et al, 2005;Narayanan et al, 2003;Narayanan and Makino, 2001;Verma et al, 2006). Through its interactions with the viralRNA, the M protein and itself, N plays important roles in virus assembly (Escors et al, 2001;Hurst et al, 2005;Narayanan et al, 2003;Narayanan and Makino, 2001;Verma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Through its interactions with the viralRNA, the M protein and itself, N plays important roles in virus assembly (Escors et al, 2001;Hurst et al, 2005;Narayanan et al, 2003;Narayanan and Makino, 2001;Verma et al, 2006). Through its interactions with the viralRNA, the M protein and itself, N plays important roles in virus assembly (Escors et al, 2001;Hurst et al, 2005;Narayanan et al, 2003;Narayanan and Makino, 2001;Verma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…M protein self-interactions occur among the transmembrane domains [49,50]. The ectodomain of the CoV M protein plays an important role in interactions with other viral proteins, such as the N protein of MHV [51,52,53], SARS-CoV [54,55,56], and TGEV [28] and the S protein of MHV [25] and SARS-CoV [13]. TGEV M aa 233–257 (AYYVKSKAAGD YSTEARTDNLSEQEK ), which contains the epitopes recognized by the mAbs 1C3 and 4C7 (underlined), is involved in M-N binding to allow virion morphogenesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on coronaviruses, including TGEV, have demonstrated that the sM protein is essential for coronavirus particle assembly (6). Coronaviruses are assembled intracellularly at membranes of the intermediate compartment, between the endoplasmic reticulum (ER) and the Golgi complex (7)(8)(9)(10)(11). The highly basic N interacts with genomic RNA to form helical nucleocapsids (12), and M interacts with nucleocapsids on cell membranes at the ER or Golgi complex (13,14).…”
Section: Introductionmentioning
confidence: 99%